Rhetoric and the Gift : Ancient Rhetorical Theory and Contemporary Communication - Mifsud, Mari Lee, 1967- (Book collections on Project MUSE., 2015)
"Examines questions in contemporary communication by turning to Aristotle's rhetorical theory and his use of Homer's idea of exchange, or gift-giving, and analyzes our conceptions of relational ethics in communication, including the ways these play out in politics, law, and culture"--